Research abuses against people of colour and other vulnerable groups in early psychedelic research. Issue 10 (12th July 2021) - Strauss, Dana; de la Salle, Sara; Sloshower, Jordan; Williams, Monnica T
Abstract : There is a growing resurgence in the study of psychedelic medicines for the treatment of mental health and substance use disorders. However, certain early investigations are marred by questionable research methods, abuses against research participants, and covert Central Intelligence Agency financial involvement. The purpose of this study was to understand how and to what extent people of colour and other vulnerable populations, specifically, individuals who were incarcerated or incapacitated due to mental health issues (inpatients with psychotic disorders), were exploited during the first wave of psychedelic research in the USA (1950–1980). To do so, we reviewed available empirical publications according to current ethical standards. Variables of interest included race and ethnicity of participants, population vulnerability, drug administration conditions, informed consent and undue influence. Our findings draw attention to the history of research abuses against people of colour in Western psychedelic research. In light of these findings, we urge a call-to-action to current psychedelic researchers to prioritise culturally inclusive and socially responsible research methods in current and future studies.